Diagnosis And Management Of Antithyroid Drug Induced Agranulocytosis - Maulina Debbyousha; Hendra Zufry (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2022)
Agranulocytosis as adversed effect of antithyroid drug (ATD) in patients with Graves disease is a rare complication but it can be serious and life threatening. The mortality rate 2-10% caused by severe infection as complications. Immediate diagnosis and management are essential for proper treatment and good prognosis. A 35-year-old female with Graves disease was complaining of fever and sore throat. She was initially treated with Thiamizole 1x20 mg for 2 weeks. Physical examination revealed leukoplakia and diffuse struma. Laboratory test : FT4 43 pmol/L, TSHs :0,005 uIu/mL, ANC <100/ul. Patient is diagnosed with ATD induced agranulocytosis. Treatment includes meropenem, fluconazole and GCSFs. The clinical and laboratory parameter improved after two weeks of treatment. Agranulocytosis in Graves’ disease patient which had ATD is a rare occurrence, with an incidence 0,2- 0,5% (66,7% had severe infection). The diagnostic criteria for agranulocytosis caused by ATD are hyperthyroid patients who are confirmed with an increase T4 and/or T3, decrease in TSH, ANC of 1500/ul before receiving ATD, ANC < 500/ul after initiation ATD and other causes of agranulocytosis have been excluded. In fact, most patients had ANC <100/ul. There are no symptom difference with agranulocytosis caused by other cause. High fever and sore throat are the most common symptom. Initial management are to identify, immediately stop the drug use, broad spectrum antibiotics and GCSFs. The hyperthyroidism will continue and alternative therapies should still be given. The best prevention is to educate patient and to examine granulocyte count frequently.